Hubungan Antara Nilai Cluster of Differentiated 4 Dengan Stadium Human Immuno Deficiency Virus Pada Ibu Hamil Yang Terinfeksi HIV/AIDS - Sulastri Sulastri; Sartini Sartini; Meida Nugrahalia (Universitas Medan Area, 2017)
Morbiditas and mortalitas caused by Human Immunodeficiency Virus (HIV) or Acquired Deficiency Syndrome (AIDS) trend increase and become an important problem peoples health in the world. Through out the 80% of children AIDS victim has a prenatal infection from their mother. The aim of this study is to know the relationship between CD4 value and HIV stadium at pregnant mother infected by HIV/AIDS. A descriptive method was applied in this experiment. The sample obtained, from 22 pregnant mothers victims diagnosed of HIV/AIDS infection in Posyansus RSUP. H. Adam Malik Medan since January 2012 until June 2013. Data obtained by measuring CD4 value before and after ARV theraphy, then statistically analyzed. The result out showed that 12 of samples (55%) have low CD4 value before ARV theraphy below 200 m3. Than, CD4 value were increased after ARV theraphy not affected by the stadium status. CD4 value before and after ARV theraphy has a negative linear corellation with HIV stadium (r = -0,743) it can be conclude that increased of CD4 value give an indirect contribution to HIV stadium victims.